2003
DOI: 10.1291/hypres.26.541
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Serum C-Reactive Protein Levels Is Associated with Obesity in Boys

Abstract: This study aimed to reveal the relationships among C-reactive protein (CRP), obesity, blood pressure (BP), and serum lipids in children. Eighty-six obese and 58 non-obese boys aged an average of 11.2 years were examined. Serum CRP levels were measured by high sensitivity latex turbidimetric immunoassay and subjects with CRP levels below 0.3 mg/dl were adopted. Comparisons of serum CRP levels, BP, and serum than 10% over the last two decades (2) and this also constitutes a serious public health problem. It is w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
39
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 24 publications
11
39
1
4
Order By: Relevance
“…Previous studies have shown similar results in young overweight and obese individuals [7,8,[11][12][13][14]18]. However, the values of hs-CRP obtained in our study are higher as compared to some previous observations [11]. In the study by Hiura et al, mean CRP values were 0.33 and 1.20 mg/L in non-obese and obese groups respectively; this may be due to exclusion of children with high hs-CRP values in the obese group assuming the possibility of acute infection.…”
Section: Correlation Between Hscrp and Other Parameterssupporting
confidence: 73%
See 4 more Smart Citations
“…Previous studies have shown similar results in young overweight and obese individuals [7,8,[11][12][13][14]18]. However, the values of hs-CRP obtained in our study are higher as compared to some previous observations [11]. In the study by Hiura et al, mean CRP values were 0.33 and 1.20 mg/L in non-obese and obese groups respectively; this may be due to exclusion of children with high hs-CRP values in the obese group assuming the possibility of acute infection.…”
Section: Correlation Between Hscrp and Other Parameterssupporting
confidence: 73%
“…Previous studies have shown similar results in young overweight and obese individuals [7,8,[11][12][13][14]18]. However, the values of hs-CRP obtained in our study are higher as compared to some previous observations [11].…”
Section: Correlation Between Hscrp and Other Parameterssupporting
confidence: 55%
See 3 more Smart Citations